The first glycine‐to‐tryptophan substitution in the COL1A1 gene identified in a patient with progressively‐deforming Osteogenesis imperfecta - Kinga Sałacińska; Izabela Michałus; Iwona Pinkier; Lena Rutkowska; Danuta Chlebna‐Sokół; Elżbieta Jakubowska‐Pietkiewicz; Łukasz Kępczyński; Dominik Salachna; Agnieszka Gach (Molecular Genetics & Genomic Medicine, 2022)
Abstract Background Osteogenesis imperfecta (OI) is a genetic disorder of connective tissue with variable phenotype and heterogeneous genetic background. Majority of reported mutations are glycine substitutions, whose clinical outcome ranges from mild to perinatal lethal. The phenotype appears to be influenced by the properties of amino acid side chain and the degree of structural aberration of collagen molecules. Since the genotype–phenotype correlation remains unclear, the severity of mutation is mostly predicted according to previously‐reported cases. Although the number of OI variants is constantly expanding, no glycine‐to‐tryptophan substitutions have been reported in COL1A1 gene. Methods A sample from a 15‐year‐old girl presenting with progressively‐deforming OI type III was tested using an NGS custom gene panel. Multiple bioinformatic and interpretation tools, including mutation databases and conservation analysis, were used for variant classification. The presence of the mutation was verified by Sanger sequencing. Results A novel heterozygous mutation c.733G>T was identified in the COL1A1 gene (p.Gly245Trp). Conclusions The discovery of this novel glycine‐to‐tryptophan substitution located in the COL1A1 gene broadens the spectrum of mutations underlying this rare disease and provides useful information on the clinical outcome of such substitutions.